Epistemology and Methodology of Comparative Law. - Van Hoecke, Mark (Hart Pub., 2004)
Whereas many modern works on comparative law focus on various aspects of legal doctrine, the aim of this book is more theoretical - to reflect on comparative law as a scholarly discipline, and in particular its epistemology and methodology. It seeks answers to fundamental, scientific problems of comparative research.